Evaluation of torque loss in Co-Cr castable abutments after cyclic loading - Somayeh Zeighami; Marzieh Alikhasi; Maryam Memarian; Moeen Hosseini Shirazi (Tehran University of Medical Sciences, 2018)
Background and Aims: For the clinical success of implant-retained prostheses, fitness of matching components and stability of the applied torque to the implant-abutment assembly under dynamic occlusal loading is essential. The aim of this study was to evaluate the torque loss in Co-Cr castable abutments after cyclic loading. Materials and Methods: 10 castable abutments were cast in Co-Cr alloy with similar size and height. Each specimen was mounted vertically on a separated implant using a 30 Ncm tightening torque. The detorque values of the abutments were evaluated after 10 min. The same tightening torque was applied to the abutments on their corresponding implants and cyclic loading was applied for 500,000 cycles to the implant-abutment assembly. The torque values after cyclic loading were recorded for each specimen. T-test analysis was conducted on scores from the groups. Resultes: The results of this study showed that the percentage of torque loss in castable abutments was significantly increased after cyclic loading (P<0.001). Conclusion: Misfit between the castable implant components can cause torque loss before and after cyclic loading. However, it is more appropriate to relate the results of this study to the screw loosening of the above mentioned abutments than judging their clinical performance.